2017
DOI: 10.3390/ijerph14030260
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Classifying Pollution Hotspots to Guide Watershed Management in a Large Multiuse Watershed

Abstract: In many locations around the globe, large reservoir sustainability is threatened by land use change and direct pollution loading from the upstream watershed. However, the size and complexity of upstream basins makes the planning and implementation of watershed-scale pollution management a challenge. In this study, we established an evaluation system based on 17 factors, representing the potential point and non-point source pollutants and the environmental carrying capacity which are likely to affect the water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Results showed that the overall level of water pollution at the Qilhai Wetland Reserve was quite serious, with the key driving factors identified as: Emissions of large amounts of pollutants : Most villagers in the vicinity of the wetlands area rely on aquaculture and fisheries for a living, therefore pesticides, fertilizers and farming cause significant levels of non-point source pollution [ 70 ]. These pollution sources and domestic sewage are all discharged into wetland waters, causing COD, TP, TN and other indicators to increase significantly, which also increases the degree of eutrophication [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that the overall level of water pollution at the Qilhai Wetland Reserve was quite serious, with the key driving factors identified as: Emissions of large amounts of pollutants : Most villagers in the vicinity of the wetlands area rely on aquaculture and fisheries for a living, therefore pesticides, fertilizers and farming cause significant levels of non-point source pollution [ 70 ]. These pollution sources and domestic sewage are all discharged into wetland waters, causing COD, TP, TN and other indicators to increase significantly, which also increases the degree of eutrophication [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that the most frequent node was sustainable development, with an appraisal rate of 238. Other indicators were as follows: resource and environment constraints, infrastructure, ecological civilization, urban security, public services, science and technology, and social culture [8,15,20,23,25]. Table 2 revealed the nodes of urban comprehensive carrying capacity, which consists of the elements related to urban comprehensive carrying capacity.…”
Section: Methodsmentioning
confidence: 99%
“…The urban comprehensive carrying capacity is not a static and fixed value but a dynamic and improvable one, with economics, human preferences, technology, and society changing. Previous studies have contributed to the understanding of urban carrying capacity, and single-element carrying capacity studies have been conducted, mainly focused on the quantitative analysis of water, land, environment, resources, and culture [8,9,10,11]. Previous studies have contributed to the definition, implementation, and the evaluation of the carrying capacity to improve urban sustainable development, especially for coastal cities with their own rich economies and resources.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the improvement of point source pollution control levels, agricultural non-point source (AGNPS) pollution arising from various sources is already more and more serious, which has become a key factor affecting water environment security [1]. In an environment where point sources are effectively controlled, non-point source (NPS) pollution is considered to be the main factor causing the deterioration of water quality [2]. NPS pollution has gradually become a major regional and global environmental problem, which has attracted more and more attention around the world [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%